Identification of mutation resistance coldspots for targeting the SARS‐CoV2 main protease. Issue 4 (22nd March 2021) - Krishnamoorthy, Navaneethakrishnan; Fakhro, Khalid
Abstract: Mutations in the novel coronavirus SARS‐CoV2 are the major concern as they might lead to drug/vaccine resistance. In the host cell, the virus largely depends on the main protease (M pro ) to regulate infection hence it is one of the most attractive targets for inhibitor design. However, >19, 000 mutations in the M pro have already been reported. The mutations encompassing 282 amino acid positions and these "hotspots" might change the M pro structure, activity and potentially delay therapeutic strategies targeting M pro . Thus, here we identified 24 mutational "coldspots" where mutations have not been observed. We compared the structure–function relationship of these coldspots with several SARS‐CoV2 M pro X‐ray crystal structures. We found that three coldspot residues (Leu141, Phe185, and Gln192) help to form the active site, while seven (Gly2, Arg4, Tyr126, Lys137, Leu141, Leu286, and Leu287) contribute to dimer formation that is required for M pro activity. The surface of the dimer interface is more resistant to mutations compared to the active site. Interestingly, most of the coldspots are found in three clusters and forms conserved patterns when compared with other coronaviruses. Importantly, several conserved coldspots are available on the surface of the active site and at the dimer interface for targeting. The identification and short list of these coldspots offers a new perspective to target the SARS‐CoV2 M pro while avoiding mutation‐based drug resistance.